A Review Article on Dadru w.s.r. to Fungal Infection - Verma, Poonam; Sharma, Ravi (International Research Journal of Ayurveda & Yoga, 2024)
Skin is the outermost covering of the body and largest organ of body, with a total area of about 20 square feet, which protects us from microbes and the elements, helps regulate body temperature and permits the sensation of touch, heat and cold. There are many skin disease in present time but Dadru (Fungal infection) is one of the common skin disease mentioned in Ayurveda. Dadru can correlate with tinea also known as Fungal skin infection in modern medicine system. Excessive severe itching and round red patches are the common clinical manifestation. 10-20% KOH and fungal culture are the specific tools for diagnosis of fungal infection. In Ayurvedic classics Virechana (Purgation) Raktamokshna (Bloodletting) and Shamana chikitsa (Pacification therapy) will be help to cure Dadru (Fungal infection). Here we will discuss about Nidana (causative factors), Samprapti (etiopathogenesis), Lakshan (clinical features), Chikitsa (treatment), Pathya-Apathya and preventive methods of Dadru kushta (Fungal infection).